2011
DOI: 10.1590/s0037-86822011005000017
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and risk factors associated with infection by Toxoplasma gondii in goats in the State of Alagoas, Brazil

Abstract: Introduction: Goats are considered very susceptible to infection by Toxoplasma gondii and when this occurs during pregnancy, it may cause fetal death with subsequent fetal resorption, abortion, mummification, stillborn or the birth of weak goats. The objective of this work was to determine the occurrence of and identify risk factors for T. gondii infection in goats in different mesoregions in the State of Alagoas. Methods: The research was conducted on 24 goat breeding farms in 10 municipalities. A total of 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
4
19
1
7
Order By: Relevance
“…The number of positive animals was also higher in farms that raised animals extensively or semi-intensively as compared to intensively managed farms. Animals fed extensively have a greater risk of coming in contact with oocysts present in cat feces, which enhances the risk of acquiring T. gondii infection [33]. A similar trend has also been reported in sheep in previous studies [34,35,36] The current study also showed a higher number of positive animals in farms where cats were present in the vicinity as compared to farms where no cats were present.…”
Section: Discussionsupporting
confidence: 89%
“…The number of positive animals was also higher in farms that raised animals extensively or semi-intensively as compared to intensively managed farms. Animals fed extensively have a greater risk of coming in contact with oocysts present in cat feces, which enhances the risk of acquiring T. gondii infection [33]. A similar trend has also been reported in sheep in previous studies [34,35,36] The current study also showed a higher number of positive animals in farms where cats were present in the vicinity as compared to farms where no cats were present.…”
Section: Discussionsupporting
confidence: 89%
“…Animals reared under extensive system had more chances to be in contact with oocysts of T. gondii excreted in F. catus faeces. Therefore, these animals had greater chances of infection (Anderlini et al, 2011). Similar to these studies, the same reason may also be responsible for higher infection in B. indicus reared under extensive management system at the present.…”
Section: Discussionsupporting
confidence: 72%
“…It yielded four risk factors. Only one of them accorded with results of the studies regarding risk factors of particular abortifacient infections conducted by other authors (Neto et al 2008, Abo-Shehada and Abu-Halaweh 2010, Anderlini et al 2011, Cantas et al 2011, Abu-Dalbouh et al 2012) -regular veterinary supervision was negatively associated with frequent fetal loss. It is possible that regular veterinary visits help farmers to deal with health problems of a herd more effectively, providing them with practical assistance and education.…”
Section: Discussionmentioning
confidence: 77%
“…A few studies have been carried out to identify risk factors for particular abortifacient infections, namely C. burnetii (Cantas et al 2011), T. gondii (Neto et al 2008, Anderlini et al 2011, Abu-Dalbouh et al 2012 and N. caninum (Abo-Shehada and Abu-Halaweh 2010). They allowed to identify contact with dogs and cats, extensive and semi-intensive herd management, poor hygiene and lack of mineral and vitamin supplementation as risk factors.…”
Section: Introductionmentioning
confidence: 99%